PENERAPAN STRATEGI DELIVERY YANG BEROREANTASI PADA TUJUAN UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN PKn SISWA KELAS V SDN 009 AIR EMAS KECAMATAN UKUI - Santika Juwito (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by the low Civics learning outcomes of fifth-grade students at SDN 009 Air Emas. The poor learning outcomes were indicated by the fact that out of 30 students, only 15 achieved learning mastery, with an average score of 45.50. In response to this condition, the researcher conducted a classroom action research study aimed at improving students’ Civics learning outcomes through the implementation of a learning strategy oriented toward Delivery at Destination. The study was carried out over two cycles. The data collected consisted of teacher and student activity data as well as students’ Civics learning outcomes. The results of the study demonstrate that students’ Civics learning outcomes improved in each cycle. This improvement is characterized by: (a) increased teacher activity in every cycle, where in Cycle I Meeting I the teacher activity score reached 6 (37.50%), increased to 8 (50.00%) in Cycle I Meeting II, rose to 10 (62.50%) in Cycle II Meeting I, and further increased to 14 (87.50%) in Cycle II Meeting II. In addition, student activity also showed consistent improvement, with a score of 9 (56.25%) in Cycle I Meeting I, increasing to 10 (62.50%) in Cycle I Meeting II, rising to 12 (75.00%) in Cycle II Meeting I, and reaching 15 (93.75%) in Cycle II Meeting II. Furthermore, (b) student learning mastery and Civics learning outcomes increased across each cycle. At the baseline, only 15 students (50.00%) achieved mastery with an average score of 45.50. In Cycle I, the number of students achieving mastery increased to 25 students (83.00%) with an average score of 76.50. In Cycle II, learning mastery further improved, with 28 students (93.00%) achieving mastery and an average score of 82.25. These findings indicate that the implementation of a Delivery at Destination–oriented learning strategy effectively enhances both student engagement and Civics learning outcomes in elementary school settings.